2021
DOI: 10.17826/cumj.780582
|View full text |Cite
|
Sign up to set email alerts
|

Screen time of preschool children in relation to their parents screen usage habits and family functions

Abstract: The aim of this study was to investigate the screen time of preschool children in relation to their parents' screen-use habits and family functions. Materials and Methods: We included 198 parents whose children were attending a kindergarten in Sarıçam district of Adana. Data were collected using a questionnaire and the Family Assessment Scale. Screen times were calculated by adding up the time spent in front of tablets, TV, mobile phones, and computers. Results: The screen times were >2 h in 57.6% children on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(40 reference statements)
1
2
0
2
Order By: Relevance
“…These results support findings from other studies (Çelik et al, 2021 ; Socias et al, 2020 ) where it is observed that families with older children from lower SES were less likely to comply with the recommendation of pediatric associations’ zero screen time recommendations. This could be due to several factors including (a) lack of knowledge about how screens could affect early development, (b) lack of parents regulation or stressful environments that could decrease the probability of controlling parents care (Çelik et al, 2021 ), (c) greater concerns about neighborhoods and safety with less access to alternative activities, and (d) less access to resources and daycare (Aguilar-Farias et al, 2021 ; Tandon et al, 2012 ). However, it is important to note that overall rates of screen use were low across our sample and more work may be helpful to better understand how and why parents are using screen time across different contexts.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results support findings from other studies (Çelik et al, 2021 ; Socias et al, 2020 ) where it is observed that families with older children from lower SES were less likely to comply with the recommendation of pediatric associations’ zero screen time recommendations. This could be due to several factors including (a) lack of knowledge about how screens could affect early development, (b) lack of parents regulation or stressful environments that could decrease the probability of controlling parents care (Çelik et al, 2021 ), (c) greater concerns about neighborhoods and safety with less access to alternative activities, and (d) less access to resources and daycare (Aguilar-Farias et al, 2021 ; Tandon et al, 2012 ). However, it is important to note that overall rates of screen use were low across our sample and more work may be helpful to better understand how and why parents are using screen time across different contexts.…”
Section: Discussionsupporting
confidence: 91%
“…However, it has been shown that SES variables such as the educational level of mothers and fathers may relate to how often this media is used, with a decrease in screen use as parent's education increases. In turn, as the economic situation of families improves, the time children use screens per week is reduced, but it is not always statistically significant (Aguilar-Farias et al, 2021;Çelik et al, 2021;Tandon et al, 2012).…”
Section: Digital Media and Development During The First Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sosyal öğrenme kuramcısı olarak bilinen Bandura, çocuklarda gelişimsel dönemde gözlem yolu ile öğrenmelerin gerçekleştiğini ve sosyal çevresinde gözlemlediği davranışları modelleyeceği görüşünü savunmaktadır (Bacanlı, 2003). Yapılan çalışmalarda da anne ve babanın ekran kullanım süresi ile çocuğun ekran kullanımı arasında ilişki olduğu anne ve babanın ekran kullanım süresi arttıkça çocuğun da ekran kullanım süresi arttığı belirlenmiştir (Çelik, 2017;Jago vd., 2012;Kubik, 2017). Ebeveynin telefon kullanımında olumsuz model olması ile akıllı telefon kullanım süresinin pozitif yönde ilişkili olduğu saptanmıştır (Manap, 2020).…”
Section: Sonuç Ve Tartışmaunclassified
“…Bu bulgu alan yazınıyla da örtüşmektedir. Araştırmalar ebeveyn eğitim seviyesi ve sosyoekonomik düzeyinin hem çocuklarının medya tüketim alışkanlıkları arasında hem de arabuluculuk tercihleri arasında bir ilişki olduğunu göstermektedir (Çelik, Yelda ve Özcan, 2021;Valcke vd., 2010;Wang, Bianchi ve Raley, 2005). Örneğin; Rideout ve Hamel (2006) tarafından yapılan araştırma, eğitim ve sosyoekonomik statüleri düşük olan ebeveynlerin çocuklarının varlıklı ve daha yüksek eğitimli ebeveynlerin çocuklarından çok daha fazla televizyon izlediğini ve daha fazla video oyunu oynadığını göstermektedir.…”
Section: Dijital Ebeveynlik Puanlarıunclassified